Pengembangan Mutimedia Pembelajaran IPA Terpadu berbasis Adobe Flash Profesional CS4 pada Materi Zat Padat di Alam - Luh Sukariasih; La Sahara; La Ode Nursalam; La Tahang (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The use of multimedia is very supportive of the continuity of the learning process in the classroom. The objective of this study is to create multimedia of learning science-based integrated Adobe Flash CS4 Professional. This multimedia was developed by adopting a model of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). This multimedia product development takes the topic of solid matter in nature. The process begins with the stage of development of Analysis, Design, Development, Implementation, and Evaluation. Before the product was used, the product development previously validated in aspects of media, material and learning, each of which involves two validators. Moreover, a limited test was conducted on two teachers and 16 students. The results of the analysis by the validator stated that adobe flash-based multimedia professional CS4 was categorized valid. While the practicality test results by teachers and students obtained that adobe flash professional learning CS4 multimedia is said to be practical because it has met the practicality standard with the percentage by the teacher of 77.22 & students 89.1%.Therefore, multimedia learning by using Adobe Flash CS4 Professional is feasible to use